2008
DOI: 10.1210/en.2007-1634
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 8 Signaling through Fibroblast Growth Factor Receptor 1 Is Required for the Emergence of Gonadotropin-Releasing Hormone Neurons

Abstract: GnRH neurons are essential for the onset and maintenance of reproduction. Mutations in both fibroblast growth factor receptor (Fgfr1) and Fgf8 have been shown to cause Kallmann syndrome, a disease characterized by hypogonadotropic hypogonadism and anosmia, indicating that FGF signaling is indispensable for the formation of a functional GnRH system. Presently it is unclear which stage of GnRH neuronal development is most impacted by FGF signaling deficiency. GnRH neurons express both FGFR1 and -3; thus, it is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(153 citation statements)
references
References 33 publications
12
139
1
1
Order By: Relevance
“…Our current study showed that the two KS-related mutations of anosmin-1, E514K and F517L, resulted in decreased binding affinity to FGFR1, which in combination with the potentially altered protein stability/expression in vivo may contribute to the phenotype of KS. FGF8 has been currently identified as one of six KS genes (47,48). It is reasonable to assume that anosmin-1 can regulate FGF8⅐FGFR1⅐HS signaling complex formation in a manner similar to that proposed here.…”
Section: Discussionsupporting
confidence: 53%
“…Our current study showed that the two KS-related mutations of anosmin-1, E514K and F517L, resulted in decreased binding affinity to FGFR1, which in combination with the potentially altered protein stability/expression in vivo may contribute to the phenotype of KS. FGF8 has been currently identified as one of six KS genes (47,48). It is reasonable to assume that anosmin-1 can regulate FGF8⅐FGFR1⅐HS signaling complex formation in a manner similar to that proposed here.…”
Section: Discussionsupporting
confidence: 53%
“…Qualitatively, GnRH neurons, although in reduced numbers, could be found throughout their normal anatomical distribution (Tsai et al, 2005;Gill and Tsai, 2006), arguing that FGF signaling does not play a role in determining when or where GnRH neurons cease migration. It has recently been shown that FGFR1 knockouts lack GnRH neurons, indicating that FGF signaling affects differentiation rather than migration (Chung et al, 2008). However, whether FGF signaling affects all progenitors equally, or additionally acts later to regulate migration is unknown, and will have to be addressed with more sophisticated genetic tools.…”
Section: Discussionmentioning
confidence: 99%
“…In Prokr2 or Prok2 homozygous knockout mice, and mice carrying Fgfr1 or Fgf8 hypomorphic mutations in the homozygous state, however, the migration of these cells is disrupted too. 14,65,79,80 The mechanism of the putative defect of GnRH cell migration in KS is still conjectural. It could be either a consequence of the early degeneration of olfactory nerve and terminal nerve axons, which act as guiding cues, or a process directly affecting the GnRH cells themselves.…”
Section: Pathophysiologymentioning
confidence: 99%
“…It could be either a consequence of the early degeneration of olfactory nerve and terminal nerve axons, which act as guiding cues, or a process directly affecting the GnRH cells themselves. Moreover, defects in GnRH cell fate specification, differentiation, axon elongation, or axon targeting to the hypothalamus median eminence may also contribute to the GnRH deficiency, at least in the KAL2 genetic form of the disease (see reference 35,80 ).…”
Section: Pathophysiologymentioning
confidence: 99%